Rodas de conversa no projeto "Vivências em atividades diversificadas de lazer": sistematização de experiências e processos educativos - Fábis, Lúcio de Castro (Universidade Federal de São Carlos, 2019)
This work is inserted in the research line of Social Practices and Educational Process, lined on the referential frame of Epistemologies of the South, especially towards praxis of leisure, humanization and the “dialogicity” by Paulo Freire. Has as its central objective, identify, describe and comprehend the educative process that arising from the conversation circles in the context of the extension project “Living In Diversified Leisure Activities” (VADL) with children and teenagers. Based on the Experiences Systematization, methodology designed within the Latin American popular education. Intend, in this sense, to contribute for a construction and reconstruction collective practical-theoretic of these conversation circles, apprehending the formative, educative and social value, and specifics of this experience, susceptible to replications in other spaces and contexts. In analysis by phenomenological inspiration, by registrations collectively constructed, mainly by field diaries, supported by voice/video recording, emerged the following thematic categories: A) “Somebody knows the colour of the skin of God?”: alterity and diversity, adding to educational process related to the development of alterity by the contact with the diversity, the exchange of experiences and backgrounds on/by the circles, contributing to “being getting” trough prejudices and expanding comprehensions and world readings; and B) “The beauty of the combinations is that do not personify ": participation and cooperation, in the face of educational processes related to “co-laboring” in the experiences, constructed collectively and continuously through planning, reflections and evaluations and self-evaluations of activities and attitudes, including in relation to the procedures of the present research, in order to develop the autonomy and the protagonism of subjects, as well as the incessant search for coherence. In the end, projections of continuities and communications to contribute with the systematized experience itself, with the construction and valorization of the knowledge of practice, as a source of scientific knowledge, and of the systematization itself, in relation to the praxis of liberation, that can be shared, reinterpreted and reconstructed with / by other experiences, spaces and subjects.
Keywords: Rodas de conversa; Processos educativos; Dialogicidade; Conversation circles; Educative processes; Dialogicity; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO